2017
DOI: 10.1093/cid/cix111
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of All-Oral Antiviral Regimens in 996 Human Immunodeficiency Virus/Hepatitis C Virus Genotype 1–Coinfected Patients Treated in Routine Practice

Abstract: Background: Large cohorts are needed to assess HIV/HCV real-world treatment outcomes. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
52
1
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 16 publications
12
52
1
2
Order By: Relevance
“…Furthermore, the absence of information on preexisting viral variants with resistance‐associated substitutions prevented us from analyzing their prevalence and their impact on treatment outcomes . Nevertheless, to our knowledge, Madrid‐CoRe is the largest real‐world study of interferon‐free regimens in HIV/HCV‐coinfected patients reported to date, with two and a half times more patients than the large series recently reported from the Veterans Administration Health Care System (996 patients) and almost 6 times more patients than all other reported series (<400 patients) . This huge sample, which compares favorably with the large real‐world studies reported for HCV‐monoinfected patients, gave us the opportunity to assess treatment outcomes for various regimens against different genotypes in different liver disease categories and to evaluate predictors of treatment response, which is difficult to assess for a therapy with failure rates <10%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the absence of information on preexisting viral variants with resistance‐associated substitutions prevented us from analyzing their prevalence and their impact on treatment outcomes . Nevertheless, to our knowledge, Madrid‐CoRe is the largest real‐world study of interferon‐free regimens in HIV/HCV‐coinfected patients reported to date, with two and a half times more patients than the large series recently reported from the Veterans Administration Health Care System (996 patients) and almost 6 times more patients than all other reported series (<400 patients) . This huge sample, which compares favorably with the large real‐world studies reported for HCV‐monoinfected patients, gave us the opportunity to assess treatment outcomes for various regimens against different genotypes in different liver disease categories and to evaluate predictors of treatment response, which is difficult to assess for a therapy with failure rates <10%.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported on the real‐world safety and effectiveness of DAAs in coinfected individuals. However, except for a report from the Veterans Affairs Health Care System on 996 patients, series are limited by small sample size or by the inclusion of specific patient groups such as those with cirrhosis or patients taking specific DAA regimens . This contrasts with real‐world cohorts comprising thousands of HCV‐monoinfected individuals treated with a wide spectrum of DAA‐based regimens …”
mentioning
confidence: 99%
“…Existing results show that certain subpopulations are still difficult to treat and the role of ribavirin and the optimal treatment duration must be clarified. Evidence suggests that patients with cirrhosis with genotypes 1b and 3 infection and those coinfected with HIV are still difficult to treat …”
Section: Resultsmentioning
confidence: 99%
“…Resulting SVR rates were 92.1% and 86.3% for sofosbuvir/ledispavir without (n = 685) and with ribavirin (n = 131), respectively, and 88.9% and 88.7% for ombitasvir/paritaprevir/ritonavir plus dasabuvir without (n = 27) and with ribavirin (n = 62), respectively. The SVR was 85.9% and 92.4% in those with (n = 205) and without cirrhosis (n = 700), respectively . These results support EASL guidelines, which indicate that the ombitasvir/paritaprevir/ritonavir plus dasabuvir regimen has potential drug–drug interactions with several antiretroviral drugs .…”
Section: Efficacy In the Real‐world Settingmentioning
confidence: 99%
“…Infatti i pazienti coinfetti avevano tradizionalmente tassi di risposta più bassi al trattamento con peginterferone e ribavirina rispetto agli individui senza infezione da HIV. Viceversa, numerosi studi hanno dimostrato un'efficacia dei regimi antivirali contenenti DAAs paragonabile a quello osservata nei pazienti monoinfetti (6)(7)(8)(9). Pertanto, i risultati di studi su nuovi regimi a base di antivirali ad azione diretta, ottenuti in pazienti con sola infezione da HCV, possono essere estrapolati per valutare la possibile efficacia nei pazienti coinfetti HIV/HCV.…”
unclassified